Warriors. Exile from Shadowclan - Hunter, Erin; Jolley, Dan (Harper Alley, an imprint of HarperCollinsPublishers, 2022)
"On the verge of a bitter leaf-bare, ShadowClan stands on the brink of its own destruction. When battle-obsessed Brokenstar banishes Nightpelt and the rest of ShadowClan's elders to the farthest edges of Clan territory, Nightpelt is shocked at his cruelty. But he's determined to ensure he and his fellow exiles survive the coming frost--and live to reclaim a ShadowClan that takes care of its own. Set during the events of Warriors: The Prophecies Begin, this is [a] . . . stand-alone adventure"--Provided by publisher.